The Unsolved Jigsaw Puzzle of the Immune Response in Chagas Disease - Acevedo, Gonzalo R.; Girard, Magalí C.; Gómez, Karina A. (Frontiers in Immunology, 2018)
Trypanosoma cruzi interacts with the different arms of the innate and adaptive host's immune response in a very complex and flowery manner. The history of host-parasite co-evolution has provided this protozoan with means of resisting, escaping or subverting the mechanisms of immunity and establishing a chronic infection. Despite many decades of research on the subject, the infection remains incurable, and the factors that steer chronic Chagas disease from an asymptomatic state to clinical onset are still unclear. As the relationship between T. cruzi and the host immune system is intricate, so is the amount and diversity of scientific knowledge on the matter. Many of the mechanisms of immunity are fairly well understood, but unveiling the factors that lead each of these to success or failure, within the coordinated response as a whole, requires further research. The intention behind this Review is to compile the available information on the different aspects of the immune response, with an emphasis on those phenomena that have been studied and confirmed in the human host. For ease of comprehension, it has been subdivided in sections that cover the main humoral and cell-mediated components involved therein. However, we also intend to underline that these elements are not independent, but function intimately and concertedly. Here, we summarize years of investigation carried out to unravel the puzzling interplay between the host and the parasite.